The organization of organizational discourse - Prichard GC (Sage, 2006)
Discourse, as Fairclough, Graham, Lemke, and Wodak (2004) noted in the introduction to their new journal, Critical Discourse Studies, is now well established as a category in social sciences. And yet, as they also note, we find significant differences as to what discourse and discourse analysis refer. These differences are, they argue, because of different theoretical, academic, and cultural traditions and how these traditions "push discourse in different directions" (2004:4). In this review essay I sketch out the key direction that discourse has been pushed or pulled in organization studies. To set the scene, I review two books that seek to advance our understanding of discourse and language analysis in organization studies. Each has its strengths, but both are relatively disengaged from the journal literature in the same field. In response to this weakness, I present a brief, citation-based examination of discourse analysis in the management and organization studies field. This analysis brings to light eight different streams of work that are underway.
Keywords: Organisational discourse analysis